Redirecting Metabolic Flux towards the Mevalonate Pathway for Enhanced β-Carotene Production in M. circinelloides CBS 277.49. (29th December 2020) - Naz, Tahira; Nazir, Yusuf; Nosheen, Shaista; Ullah, Samee; Halim, Hafiy; Fazili, Abu Bakr Ahmad; Li, Shaoqi; Mustafa, Kiren; Mohamed, Hassan; Yang, Wu; Song, Yuanda
Abstract : Carotenoids produced by microbial sources are of industrial and medicinal importance due to their antioxidant and anticancer properties. In the current study, optimization of β -carotene production in M. circinelloides strain 277.49 was achieved using response surface methodology (RSM). Cerulenin and ketoconazole were used to inhibit fatty acids and the sterol biosynthesis pathway, respectively, in order to enhance β -carotene production by diverting metabolic pool towards the mevalonate pathway. All three variables used in screening experiments were found to be significant for the production of β -carotene. The synergistic effect of the C/N ratio, cerulenin, and ketoconazole was further evaluated and optimized for superior β -carotene production using central composite design of RSM. Our results found that the synergistic combination of C/N ratios, cerulenin, and ketoconazole at different concentrations affected the β -carotene productions significantly. The optimal production medium (std. order 11) composed of C/N 25, 10  μ g/mL cerulenin, and 150 mg/L ketoconazole, producing maximum β -carotene of 4.26 mg/L (0.43 mg/g) which was 157% greater in comparison to unoptimized medium (1.68 mg/L, 0.17 mg/g). So, it was concluded that metabolic flux had been successfully redirected towards the mevalonate pathway for enhanced β -carotene production in CBS 277.49.